What is the Best Mix of Policies for Canada's Children?: An International Comparison of Policies and Outcomes for Young Children - Shelley Phipps (Luxembourg Income Study (LIS), 1999)
The goal of this project is to explore possible linkages between social policy mix and outcomes for young children (i.e., aged 0 to 11 years) in Canada, the Netherlands, Norway, the UK and the US. Of course, social policy is obviously not the only potential determinant of children's well-being. Some children are likely to be affected by almost any policy enacted (or not enacted) in any country. For example, monetary and fiscal policy, by affecting levels of interest rates and unemployment in the country will affect the well-being of some children whose parents may or may not be able to afford to buy a house, whose parents may or may not find paid employment. The characteristics of the unemployment insurance program will be vitally important for the well-being of some children whose parents face unemployment. However, since it is obviously not possible to consider every policy available in one country, let alone five countries, this study will focus on social policies explicitly designed with young children in mind. Further, since the analysis is quantitative in nature, the focus is primarily on the tax and transfer programs available in the 5 countries which can more easily be studied using quantitative techniques.
Keywords: 330; Jugendpolitik; Sozialpolitik; Policy-Mix; Großbritannien; Kanada; Niederlande; Norwegen; USA